Polovoi dimorfism i individual'nye osobennosti razvitiya koordinatsionnykh sposobnostei vysokokvalifitsirovannykh sportsmenov vostochnykh edinoborstv - Sadovski, E. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the displays of sexual dimorphism in individual pecularities of the coordination capacities in elite athletes of eastern single combats. The high informativety of the computer and laboratory tests defining various coordination capacities of elite athletes representing types of eastern single combats had been started. The female representatives of eastern combats demonstrated the advantage in tests of hands movements coordination in the accuracy of reproduction and differentation of space movements parameters and in balance keeping. The males athletes were more successful in tests on reactions and adaptation to complicated conditions and space orientation.